Impact of Corporate Governance on Profitability of Joint Venture Commercial Banks in Nepal: From Investor’s Perspective - Adhikari, Raja Ram (NPRC Journal of Multidisciplinary Research, 2025)
Good corporate governance has a crucial role in strengthening shareholder trust, promoting competitiveness, and ultimately driving economic growth. The study's major goal was to investigate the impact of corporate governance on the profitability of joint venture banks in Nepal. The information used in this study was gathered from primary sources using a descriptive research design. 400 individual investors were taken from the broker no. 36 and 32 situated in Putalisadak area, Kathmandu who generally hold the joint venture commercial banks' share; participated in the survey through questionnaire Google form and physically distributed while collecting responses from October 5 to 25, 2024 with purposive judgmental sampling. The majority of respondents think that non-performing loan and Board size destructively linked with profitability. On the other hand, board independence and the number of board meetings are positively correlated. To sum up, dependent variable Profitability (ROE and ROA) are significant at 1% and 5% significance level with independent variables. BOD should treat minority shareholders in equitable basis.